Постсоветская деинституционализация и становление новых социальных институтов в украинском обществе - Головаха, Е.; Панина, Н. (Социология: теория, методы, маркетинг, 2001)
The article presents an institutionalization concept in a post-soviet society. The double institutionalization phenomenon was described as specific social mechanism which supports social stability and integration under conditions when institutional bases of social life are ruining. In order to test hypotheses on specific character and tendencies of post-soviet institutionalization and new social institution formation, the author uses the data of sociological monitoring on social changes in Ukrainian society conducted by the Institute of Sociology of the NAS of Ukraine for many years.